GRADMe: Reengineering the Graduation Clearance Workflow with an Online System - Asnul, Hanisha (IRC, 2020)
The aim in this project is to develop a program for managing and systemize the manual graduation clearance form of final year students. The system will integrate via online to allow students fill up the graduation clearance form with relevant department in Universiti Teknologi PETRONAS (UTP) such as UTP Safety Department, Residential Village Department and Finance Department. The implementation framework is Web-based software with Inter-platform functionality implemented using Microsoft Intelligence Business Applications Platform (Microsoft 365). The project was implemented in two phases. During the first phase, the final semester student clearance program study process was handled. During the second phase, the system Reengineering the Graduation Clearance Workflow with an Online System (GRADMe) is develop. Research on the clearance process for the final semester at UTP, can support the project's concept. Methodology applied throughout the project is an Agile method classified into preparation, research and requirement collection, data development and documentation, prototype development, and evaluation phase. As the result of this GRADMe system, the goal of this project is to address issues concerning on running the manual program. This is planned to be used digitally, thus relieving both final year students and UTP employees of the manual method from much burden as encountered. By using visualization at the end, it can provide for a more accurate depiction of the complexities of knowledge contagion to the individual than text-based media, the interactive framework may be used as a preparation and implementation toolkit to understand the larger picture when administrators need to take decisions and measures to comply with misinformation.